Experimental Evidence of Precipitation of All 12 Variants in a Single β Grain in Titanium Alloys - Yi Chen; Hongchao Kou; Liang Cheng; Yunlong Zhang; Yun Yu; Yalin Lu; Fuxian Zhu (Advances in Materials Science and Engineering)
The effect of the changing of the local composition of the β matrix on the precipitation of the α phase has been investigated by electron backscatter diffraction (EBSD) to obtain more insight in the nucleation and variant selection of these α plates based on the Ti-5.04Al/Ti-1.52Mo (at.%) diffusion couple. The results showed that the composition gradient was formed from one side of the diffusion couple to another side after diffusion annealing. Followed by a secondary heat treatment process, it was found for the first time that all 12 variants formed in a single β grain in the diffusion zone in the Ti-5.04Al/Ti-1.52Mo diffusion couple, which indicated that the changing of the local composition of the β matrix significantly weakened the α variants selection behavior.